Changes of Anxiety Scores in Pregnant Women With Hypertension After Progressive Muscle Relaxation Therapy - Pratiwi, Rizqi Dian; Sunarjo, Lanny; Adi, Mateus Sakundarno (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Pregnant with hypertension is one of the main causes of maternal and fetal death, but efforts to resolve them have not been optimal. To determine the difference in anxiety scores by Progressive Muscle Relaxation (PMR) on pregnant women with hypertension. This study used a cross-over design. A total of 36 women in the third trimester obtained by random sampling were given PMR and bed rest. The measurement used HARS questionnaire. Data were analyzed using paired t-tets. There was a significant difference in anxiety scores before and after PMR (P <0.001), while there was no difference in bed rest (P> 0.05). There was a significant difference between PMR and bed rest on anxiety scores (P <0.001) with a greater mean reduction on PMR therapy. PMR can reduce anxiety scores in pregnant women with hypertension, so PMR can be a complementary therapy in obstetric care for them.